Factors Determining Choice of Conventional Labour Among Yam Producers in Benue State of Nigeria - Sadiq, Sanusi Mohammed; Singh, I. P.; Ahmad, M. M.; Garba, A. (Indonesian Journal of Agricultural Research, 2021)
The present research empirically determined the factors that influenced the choice of combined labour for efficient yam marketable surplus in Benue State of Nigeria. 2016 cropping season cross-sectional data elicited by structured questionnaire complemented with interview schedule from a total of 120 farmers chosen through a multi-stage sampling technique was used. The instruments used for data analysis were descriptive and inferential statistics. The empirical evidences showed that decision for choice of efficiently combined labour that is supplemented by paid labour for efficient yam marketable surplus was affected by low yam productivity and low income which largely owed to poor proceeds from product marketing. Gender stereotype due to culture and religious barriers affected women access and control to productive access, thus hinders women active involved in yam entrepreneurship as they cannot carter for paid labour. Thus, it can be inferred that utilization of combined labour was affected by poor yield, gender stereotype and poor economic capital. Therefore, for farmers to be able to harness combined labour efficiently for a good marketable surplus, thus a better wellbeing for farmers, farmers need technical guided on potential yield; provision of buffer stocks for a remunerative price normalization; and, breaking the jinx of gender inequality through tacit sensitization in the studied area.